Architektur und Low-Power-Konzept für eine vernetzte Sensorplattform zur Erzeugung eines behaglichen und energieeffizienten Smart-Home-Umfeldes - Fehrle, Adrian; Benke, Elisabeth; Braun, Thomas; Dorscht, Felix; Hart, Manuel; Franke, Jörg (10. GMM-Fachtagung Energie Autonome Sensorsysteme EASS 2020, 2020)

Integration of electric vehicles in time-flexible charging processes through contracting models - Fehrle, Adrian; Funk, Felix; Teske, Franz; Dorscht, Felix; Franke, Jörg (2021 11th International Electric Drives Production Conference (EDPC), 2021)
The increasing popularity of electric vehicles (EVs) is leading to major challenges for utilities. The existing low-voltage grid will not be able to support the growing number of simultaneously charging vehicles and would therefore have to be expanded at high cost. In addition, these high charging phases lead to extreme demand peaks, which the utilities must meet by purchasing energy on the electricity spot market at expensive quarter-hourly rates. Through flexible charging processes controlled by the utilities, these costs could be significantly reduced. Similarly, grid utilization can be equalized by shifting the charging phases while parking to more beneficial electricity price periods. Nevertheless, it is guaranteed that there will be no comfort restrictions for the EV owner. To make this possible, EV owners have to enable the utilities to include their vehicles in the flexible charging process. In this paper, we present a contracting model for EVs, in which costumers do not buy the vehicle but lease it from the local utility instead. Reduced leasing rates incentivize end costumers to integrate their EV into the charging process optimization of the utility. Our findings show that this contracting model leads to significant cost savings for all parties involved.
Keywords: Adaptation models; Low voltage; Costs; Smoothing methods; Process control; Tariffs; Production; electric vehicles; contracting; utilities; power grids; flexibilities

Potential analysis of a cloud-based energy management system for the generation of flexibilities - Fehrle, Adrian; Teske, Franz; Dorscht, Felix; Franke, Jörg (IEEE PES Innovativ Smart Grid Technologies ISGT 2021, 2021)
The energy transition confronts utilities with major challenges due to the decentralised and volatile feed-in of renewable energies. As part of the Cloud|E research project, an intelligent cloud-based energy management system (EMS) is being developed in which flexibility options are made available to the utilities by connecting components for power generation, storage and large loads that are found in private households. The potential of this system is analysed in this paper using a simulation scenario. The individual components for generating flexibilities are considered separately. The flexibility potential is presented in the form of additional revenue opportunities on the part of the utilities. It is shown that each flexibly controlled component leads to an additional profit for the utility. By varying the framework conditions in a wide-ranging scenario analysis, the robustness of the system is proven. The results demonstrate the possibility of flexibility generation in the area of electromobility. In total, the potential of a decentralised cloud-based EMS to support the utilities in times of the energy transition can be confirme
Keywords: utility; energy management system (EMS); heat pump (HP); electric vehicle (EV); photovoltaic (PV); battery storage unit (BSU)